Studi aktivitas informal ruang jalan di kawasan Pecinan Semarang, Indonesia - Yohanes Basuki Dwisusanto; Christin Purnamasari Nusaputra (ARTEKS : Jurnal Teknik Arsitektur, 2022)
The informal aspect of daily activities plays a role in shaping the quality of urban architectural design. This is due to the fact that public open space has become a place for all community-based informal activities, thereby, making the public-private sphere a collective spectrum and using the outdoor as a common space for all. These activities, however, have the ability to create a sense of belonging to the urban community towards a place even though they are temporary. An example of this is the Semarang Chinatown area which is a street space being used as a living outdoor space (sense of place). Therefore, this study was conducted to understand the character of the outdoor living room in the street space through the sense of place dimension. This involved using qualitative methods through field observation data to identify the place identity, place attachment, and place dependence. The findings showed that the informal activities reviewed through the sense of place dimension shape the character of the outdoor living room in the street space and this is expected to increase the quality of the street as a public open space in the Semarang Chinatown area.